2014
DOI: 10.1016/j.jpainsymman.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Control Preferences, Disclosure of Information Preferences, and Satisfaction Among Hispanic Patients With Advanced Cancer

Abstract: Context Studies to determine the decisional control preferences (DCPs) in Hispanic patients receiving palliative care are limited. Objectives The aims of this study were to describe DCPs, disclosure of information, and satisfaction with decision making among Hispanics, and to determine the degree of concordance between patients’ DCPs and their self-reported decisions. Methods We surveyed 387 cancer patients referred to outpatient palliative care clinics in Argentina, Chile, Guatemala, and the U.S. DCPs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 34 publications
(32 reference statements)
5
55
0
1
Order By: Relevance
“…Finally, certain studies conducted in different patient populations suggest that patients preferred either a shared or an active decision‐making preference over a passive one . However, studies have found that patients who preferred a certain decision‐making strategy were satisfied with the way decisions were made in their care even when actual decision‐making may be different from their preferred role . Further studies investigating the preferred and perceived decision‐making role of patients and their influence in perception of different physician attributes would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, certain studies conducted in different patient populations suggest that patients preferred either a shared or an active decision‐making preference over a passive one . However, studies have found that patients who preferred a certain decision‐making strategy were satisfied with the way decisions were made in their care even when actual decision‐making may be different from their preferred role . Further studies investigating the preferred and perceived decision‐making role of patients and their influence in perception of different physician attributes would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed an encouraging trend of a lower proportion of cancer patients dying in acute care hospitals and a higher number of hospice enrollments in the last month of life, but this was dampened by findings of higher rate of ICU and hospital utilization in the last months of life and higher proportion of hospice referrals in the last 3 days of life, respectively . The studies highlight the importance of eliciting individual preferences via better communication, as there is frequent disagreement whenever physicians assume what their patients would prefer . Among cancer patients, preferences for making such decisions vary, ranging from active to passive, with shared decision‐making being the most preferred .…”
Section: Suffering At the End Of Lifementioning
confidence: 99%
“…The key to successful integration is to focus on collaboration and communication between oncologists and PC clinicians about roles and responsibilities between those clinicians with patients and families regarding the goals of care. Current data suggest communication gaps in eliciting individual preferences for communication . Recent preliminary studies suggest the usefulness of communication aids such as prompt sheets or cards .…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…However, several researchers have observed passive attitudes toward decision-making among cancer patients; in fact, a recent research review has shown that passive attitudes remain dominant in patients 3 . Although many researchers accept the importance of shared attitudes in decision-making, these observations might be caused by differences in patient ethnicity, age 4,5 , and background experience 6 . According to a recent study, patients prefer to be controlled by the physician in decision-making; they trust their physician 7 .…”
Section: Introductionmentioning
confidence: 99%